Inflammation-induced modulation of cellular galectin-1 and-3 expression in a model of rat peritonitis - Gil, C. D.; Cooper, D.; Rosignoli, G.; Perretti, M.; Oliani, S. M. (Birkhauser Verlag Ag, 2006)
Objective and design: To investigate the effect of galectin-1 (Gal-1) and -3 (Gal-3) on leukocyte migration and analyze the expression of both galectins in inflammatory cells using a model of rat peritonitis.Material or Subjects: Sprague-Dawley rats (n = 4 per group).Treatment: Peritonitis was induced in animals through intraperitoneal injection of carrageenin (1.5 mg/kg) and rat mesenteries were analyzed at different time points (0, 4, 24 and 48h). For pharmacological treatment, rats received intravenous injection of Gal-1 or -3 (3 mu g/kg) followed by carrageenin.Methods: Western blotting and immunoelectron microscopy analysis. Statistical analysis was performed using ANOVA followed by Bonferroni test.Results: Pharmacological treatment with Gal-1, but not Gal-3, inhibited (similar to 50%) leukocyte recruitment into the peritoneal cavity at 4h time-point. In this early phase, immunogold staining of mesenteries showed a diminished Gal-3 expression in degranulated mast cells and Gal-1 in transmigrated neutrophils (similar to 20% reduction compared to intravascular cells). In the later phases (24 and 48 h), leukocyte turnover was associated with augmented Gal-1 expression in neutrophils and macrophages and Gal-3 in mast cells and macrophages.Conclusions: These results point to a balanced expression of cell-associated-Gal-1/Gal-3 and might impact on the development of new therapeutic strategies for inflammatory diseases.
Keywords: In vivo inflammation; mast cell; neutrophil; endothelial cell; macrophage